The effect of toxoplasmosis infection in the concentration of interferon-ɣ and complementary proteins C3,C4 for parasite infected woman Toxoplasma gondii - AbdulKhaliq Alwan Muheimeed Al Jubouri; Noor Talal Ali Taha Al Safe (Tikrit Journal of Pure Science, 2019)
The current study deals with measuring the level of interferon-ɣ   لfor 96 sample of infected women with Toxoplasma gondii , whose attended  Salah- El-Deen Teaching Hospital in Salah- El-Deen Governorate from 13/10 /201  to 2017/4/20 . The samples have been divided into50 50 infected pregnant  women with  ToxoplasmagondiiToxoplasma gondii and 46 women as a control group which included 23 pregnant women 23and 23  non – pregnant  whose as  not infectedT.gondii. The study shows significant difference in the level of interferon between the infected women group  and control group .The level of interferon ɣ in infected women was higher compared with the control group 1.658 0.977 0.977 and ) (,ah 0.7650.765 0.524 0.524)  pg. / ml, respectively, at the level of probability 0.01p< .0.01>p concerning on to the measurement of the level of the complementary proteins C3 ,C4)C3, C4),It was shown the result exist variances moral if were valued in infection women ​​ofC3,C4) 0.3708 0.0107 0.0107 and) ( 0.38510.3851 0.0306 0.0306) mg/dl, respectively, compared to the valued in non-infection women0.2528 0.2528  0.0463 0.0463 and) ( 0.2142 0.2142 0.06080.0608) mg/ dl, respectively, at the level of probability 0.01 p<. 0.01. >